Beyond counting: Unveiling epistemic gaps and learning obstacles in Indonesian first-grade mathematics textbooks - Sholikhakh, Rizqi Amaliyakh; Oktaviani, Dian Nataria; Albab, Ulil; Wahyuni, Astri (Indonesian Journal of Science and Mathematics Education, 2025)
This study aims to analyze number recognition material (0–10) in Indonesian first-grade mathematics textbooks under the Kurikulum Merdeka using a praxeological lens from the Anthropological Theory of the Didactic (ATD). The research method employed was qualitative document analysis of the official textbook published by the Ministry of Education’s Center for Curriculum and Educational Standards. Through this method, the researchers examined tasks (T), techniques (τ), technology (θ), and theory (Φ) to identify epistemic structures and potential learning obstacles embedded in the material. Results show that although the macro-organization of the four main task types is reasonable, the micro-level design is weak. Task sequences often disrupt logical learning trajectories and rely heavily on perceptual and operational techniques, with limited progression toward introspective and a priori reasoning. Technological justifications and theoretical underpinnings remain largely implicit, hindering robust conceptual understanding and generating didactical and epistemological obstacles, particularly regarding zero and the distinction between numbers and numerals. Comparisons with textbooks from high-performing systems highlight shortcomings in epistemic framing, representational coherence, and cognitive demand. The study's implications include providing an integrated praxeological–learning obstacle framework and recommending improvements in textbook design, teaching practice, and policy to enhance students’ epistemic access to elementary mathematics.